Kepemimpinan Entrepreneur Pendeta dalam Memberdayakan Kewirausahaan Anggota Jemaat - Inriani, Eva; Lestaria, Farmingga; Sorongan, Radea Delataka (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
One of the church's responsibilities in the era of disruption is to strive for economic independence for the church and its congregation members. The aim of this study is to reveal the entrepreneurial leadership style of the pastor of GBI Hope Rayon 8 Palangka Raya and the pastor's entrepreneurial leadership strategy in empowering the entrepreneurship of congregation members. This article was prepared using qualitative research methods, with descriptive research type. This article shows that in implementing entrepreneurial leadership at GBI Hope Rayon 8 Palangka Raya, where the majority of the congregation members are young people, as an appropriate approach, the pastor collaborates entrepreneurial leadership styles, paternalistic leadership styles and democratic leadership styles so that entrepreneurship among the congregation members can run well. The pastor's entrepreneurial leadership strategies implemented include talent identification and development, effective communication, decision-making, motivation and inspiration, utilizing business potential within the congregation, and implementing marketing or business promotion strategies through pamphlets, print media and social media.